Antihypertensive activity of a new c-Jun N-terminal kinase inhibitor in spontaneously hypertensive rats; Hypertension Research; Vol. 43 - Plotnikov M. B. Mark Borisovich; Aliev O. I. Oleg Ibragimovich; Shamanaev A. Yu. Aleksandr Yurjevich; Sidekhmenova A. V. Anastasiya Vitaljevna; Anishchenko A. M. Anna Mikhaylovna; Fomina T. I. Tatjyana Ivanovna; Rydchenko V. S. Victoria Sergeevna; Khlebnikov A. I. Andrey Ivanovich; Anfinogenova Ya. J. Yana Jonovna; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Atochin D. N. Dmitry Nikolaevich (2020, 2020)
Title screen